Quality of life in patients with cancer diagnosis in Brazil: a systematic review (Research, Society and Development, 2022)
It is advantageous to check the quality of life of individuals with cancer, since the treatments, signs and symptoms are the origin of some degree of emotional disturbance, physical and functional limitations that end up interfering in the individual's life. Thus, the objective was to assess the quality of life of patients diagnosed with cancer in Brazil, using studies that used validated instruments for this group of individuals. Therefore, it is a systematic review carried out according to the Guidelines of Transparent Reporting of Systematic Reviews and Meta-Analyzes (PRISMA statement) between January 2008 and August 2019 through specialized databases: PUBMED, SCOPUS, MEDLINE, LILACS and SCIELO. Being identified that the quality of life has been impaired in the physical and mental spheres. In addition, the Southeast region has the largest number of studies. Colorectal cancer was more identified in the studies, and the WHOQOL-bref instrument was the most used. Thus, the data found can become subsidies for the promotion of actions aimed at responding to the oncological needs for the control of the disease.